Using simulation as cervical and anal cytology teaching-learning strategy - Coser, Janaina; Zanella, Janice de Fátima Pavan; Diefenthäler, Vanessa Laís; Sperling, Sara Gallert; Ronchi, Dario; Mugnol, Tatiana; dos Santos, Juliana Lemes (International Journal for Innovation Education and Research, 2017)
The current descriptive study is an experience report about the use of gynecological simulators in teaching and research activities developed in the Undergraduate and Postgraduate courses in Health at Cruz Alta University in Southern Brazil. The aim of the present study is to describe the use of gynecological simulator as cervical and anal cytological sample collection teaching-learning strategy, as well as to describe the protocol adopted in such procedure. The gynecological simulator is a useful instrument applied to the sample collection practice for cervical and anal cytological examination purposes, since it is a static dummy anatomically similar to the female body. Simulating the procedure allows students to train and improve skills required to the technique; however, the theoretical contextualization must precede the practice in the simulator in order to stimulate students to reflect on all aspects involved in the exam. The use of gynecological simulator is recommended as complementary tool in cytologic examination teaching-learning scenarios.